Highly Efficient Perovskite Heterojunction Solar Cell With Dual Absorber Layers for State of Art Photovoltaic Technologies - G. Venkateswarlu; Umakanta Nanda (IEEE Access)
Perovskite solar cells (PSCs) face significant challenges, including instability, high recom- bination losses, poor charge transport, and suboptimal band alignment, which limit their efficiency and commercial viability. The previous studies relied on MoS2 as an ETL, which has poor conduction band alignment with CsPbI3, resulting in high resistance and inefficient charge extraction. This study overcomes these limitations and objectives by introducing MoSe2 as a dual absorber, leveraging advantageous characteristics such as its strong infrared absorption, high carrier mobility, enhanced band alignment, optimal layer thickness, controlled defect levels, tailored doping concentrations, and minimized interface defects, all of which improve charge carrier transport and optimize generation and recombination dynamics. Also, defect passivation at the MoSe2/CsPbI3 interface lowers the number of trap states, which lowers recombination and raises Voc. The replacement of organic HTLs with CFTS further enhances device stability and longevity. The simulation yielded remarkable photovoltaic parameters, achieving an open-circuit voltage (Voc) of 1.40 V, a short-circuit current density (Jsc) of 35.81 mA/cm2, a fill factor (FF) of 82.9%, and an exceptional power conversion efficiency (PCE) of 41.86%, approaching the Shockley-Queisser theoretical efficiency limit for heterojunction solar cells. The proposed architecture offers a roadmap for future experimental work, semiconductor device simulation, modeling in high-efficiency and stable perovskite heterojunction solar cells for next-generation photovoltaic technology.